Comparative lower back and hamstring flexibility among males and females of Malaysian colleges’ student / Tan Chee Hian and Sharunniza Sidik - Tan, Chee Hian; Sidik, Sharunniza (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2016)
The study was to compare the lower back and hamstring flexibility among males and females Malaysia College students. Fifty students (25 males and 25 females) between 18 and 23 years old were assigned to 2 groups: males and females. The tests are traditional sit-and-reach flexibility test. There were pre-test and post-test. After pre-test, subjects trained 3 times a week for 6 weeks in 4 types of static stretching condition were Lying Back Curl, Lying Knee Hug, Supine Gluteal Stretch, and Sitting Hamstring Stretch (as treatment) before the post-test. The results were analyzed for a comparison of gender differences in sit-and reach test. An independent sample t-test was used. The t-test revealed a significant between 2 groups. Both group had significant (p<0.05) improvements in the measures. The pre-test result (females 26.22 ± 6.04 cm, male 20.97 ± 4.89 cm). The post-test result ( females 28.65 ± 6.24 cm, males 23.80 ± 5.07 cm). The result showed significant between 2 groups was t = 3.372, p:0.001<0.05 for pre-test and t= 3.017, p:0.004<0.05 for post, this mean the null hypothesis was rejected. The results of the pre-test and post-test of 2 groups males and females indicated that there was significant different in mean score of lower back and hamstring flexibility between males and females of college students. Female group had significantly greater score in pre-test and post-test, but the result showed that males college student could be improved their flexibility after treatment.. The result of this study supported to/ by the previous study that females more flexible compare with males (Schell & Leelarthaepin, 1994) and (Warmbrodt & Rissman, 1999).